Uniaxial and biaxial hot pressing of PVDF films: A pathway toward high-performance piezoelectric sensors and energy harvesters - Suprapto Suprapto; Jubaidah jubaidah; Selamat Triono; Harianto Gunawan; Lisyanto Lisyanto; Aditya Sukma Nugraha; Yopan rahmad Aldori (Teknomekanik, 2026)
The piezoelectric efficiency of Poly (vinylidene fluoride) (PVDF) membranes becomes restricted by the challenge of generating and stabilizing electroactive β-phase during processing. Stretching requires control of deformation parameter, while solvent-based methods bring environmental and occupational health risks. This research suggests hot-pressing as an alternative method for enhancing β-phase fraction, utilizing multidirectional stress without solvent or chemical exposure. This study systematically compares uniaxial hot-pressing (Uniaxial HP) and biaxial hot-pressing (Biaxial HP) setups to determine which stress distribution is more effective at promoting changes and improving piezoelectric properties in PVDF membranes. The main objective of this research is to systematically evaluate and compare the impacts of uniaxial and biaxial hot-pressing on the crystalline phase transformation and electromechanical performance, including the piezoelectric coefficient (d33) and output voltage response of PVDF membranes. PVDF pellets were hot-pressed at 220o C under a pressure of 60 MPa for 15 minutes followed by rapid quenching in ice water. X-Ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) confirmed phase composition, correlated with performance via the piezoelectric coefficient (d33), and assessed piezoelectric activity. Experimental results show that biaxial loading provides a higher b-phase fraction (50.47%) compared to untreated membranes (47.80%) and UHP samples (49.30%). The crystallinity and the piezoelectric coefficient also increased to 49% and 18.8 pC/N, respectively. Biaxial stress pattern during hot-pressing induces favourable thermodynamic and kinetic conditions for b-phase expansion. Beyond phase-related results, the approach delivers competitive piezoelectric effectiveness while maintaining simplicity and reducing solvent-dependent processing steps.